A multifactor approach of the APT versus the CAPM for the UK stock market - Briffa, Christian (2008)
In an ever changing financial world, innovation in how practitioners and researchers view and study ways of better understanding the factors that are most influential are crucial. Since the seminal paper of Harry Markowitz in the 1960ÃÂÃÂ¢ÃÂÃÂÃÂÃÂs, the Capital asset pricing model has been viewed as a benchmark in correlating risk and return. The following paper attempts to identify which of the two models better explains the risk and return factors when both modelled are exposed to the FTSE 100.